Beetroot (Beta vulgaris L.) juice supplementation and hemoglobin response in head and neck cancer patients after chemotherapy - Dena Tria Andini; Benny Kurnia; Lily Setiani; Azwar Ridwan; Elvia Haroen (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Anemia frequently occurs in patients with cancer and can worsen due to chemotherapy. The literature on non-pharmacological interventions to increase hemoglobin levels in patients with head and neck cancer following chemotherapy remains limited. This study aimed to measure the effect of beetroot juice supplementation on changes in hemoglobin levels in patients with head and neck cancer who had undergone chemotherapy. Methods: An experimental study with a one-group pretest–posttest design was conducted at dr. Zainoel Abidin General Hospital, Banda Aceh (July–November 2024). The sample consisted of all head and neck cancer patients undergoing chemotherapy cycles I–VI (total sampling, n=40), divided into two treatment groups: 100 g beetroot juice (n=20) and 200 g beetroot juice (n = 20). Hemoglobin levels were measured before and 14 days after the intervention. The analysis was performed using paired t-tests and effect sizes (Cohen’s d). Results: Administration of 100 g of beetroot juice did not significantly alter hemoglobin levels, with an average difference of −0.24 g/dL (p = 0.241). In contrast, the 200-gram dose resulted in a significant increase in hemoglobin levels, with an average difference of +0.44 g/dL (p = 0.016) after 14 days of intervention. Furthermore, the estimated Cohen’s d (pooled SD) was 0.51, indicating a moderate effect. In conclusion, the administration of 200 g beetroot juice for 14 days was associated with a small but statistically significant increase in hemoglobin levels in patients with head and neck cancer who underwent chemotherapy. Further studies in the form of RCTs with larger sample sizes and stricter compliance monitoring are needed to confirm these findings and assess their clinical relevance.